PENGARUH INJEKSI STEROID LOKAL TERHADAP LATENSI DISTAL SENSORIK DAN MOTORIK PADA SINDROM TEROWONGAN KARPAL - Daniel Setiawan Wanahardja,*Andi Kurnia Bintang,* Yudy Goysal* (NEURONA, 2019)
INTRODUCTION CARPAL TUNNEL SYNDROME CTS IS THE MOST COMMON TYPE OF NEUROPATHY FOUND IN UPPER EXTREMITIES THE SYNDROME CAN CAUSE DISABILITY AND LEADS TO THE DECREASE IN PRODUCTIVITY LOCAL STEROID INJECTION CAN HELP ALLEVIATE THE SYMPTOMS DELAY OPERATION AND IMPROVE ELECTROPHYSIOLOGIC PARAMETER IN A CONCISE PERIOD